Studies on the completely mixed activated sludge treatment of fellmongery and tannery lime-sulphide effluents - Rawlings, Douglas Eric (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1977)
Industries producing highly polluted waste waters are having to purify their effluents to meet with ever increasing requirements laid down by water authorities. The South African Water Act of 1956 has prescribed a very high standard to which waste waters must conform before discharge into a South African water course. Enforcement of these standards falls under the jurisdiction of government authorities such as the Department of Water Affairs. Similarly, municipalities and other local authorities set standards with which trade effluents must comply before discharge into public sewers for treatment in a municipal sewage works. These local authorities are empowered to recover from the trader the additional costs incurred in treating trade effluents. Costs are usually levied in respect of volume, oxygen demand, settleable solids and the production of secondary sludge. In recent years, these standards have been enforced to an extent where the survival of several industries has become dependant on whether these industries are able to purify or dispose of their effluents in a manner acceptable to the water authorities. Chap. 1, p. 1.
Keywords: Tanneries -- Waste disposal; Sewage sludge -- South Africa -- Management; Sewage -- Purificiation -- Biological treatment; Water quality management -- South Africa; Water -- Purification -- Biological treatment -- South Africa